Do Productive Government Expenditures Affect Economic Growth? Evidence from Provincial Governments across Indonesia - SIJABAT, ROSDIANA (Universitas Muhammadiyah Yogyakarta, 2017)
This study is intended to examine the impacts of productive expenditures on economic growth on the 25 provinces found in Indonesia before fiscal decen- tralization (covering 1994–1997) and 33 provinces after decentralization over the period 2011-2015. The empiric approach has been implemented through a panel data approach and regression model estimated to follow the endogenous growth model of Barro (1990). The main findings of this research show that: (1) provincial governments’ productive expenditures in education promoted eco- nomic growth in the 25 pre-decentralization provinces; and (2) productive ex- penditures in the security and public order sector, health and education sector have promoted economic growth in the 33 post-decentralization provinces. From these results, it can be concluded that this study has contributed to economic literature by indicating that different types of productive government expendi- tures offer different impacts on economic growth. The policy implications which can be formulated from the results of this study are that provincial governments should promote and provide incentives for private investments in the public sec- tor because only the education sector (before fiscal decentralization) and the security and public order sector as well as the education sector (after fiscal decentralization) have a statistically significant role in promoting economic growth. This can be realized through public–private partnership, which has greatly in- creased the performance of public-sector investment around the world. Future research, using relevant control variables to estimate the effects of productive expenditures on economic growth, will provide a greater empiric contribution to the literature.